Epilepsia partialis continua: A review. (January 2017) - Mameniškienė, Rūta; Wolf, Peter
Highlights: EPC has many possible local or systemic etiologies. Motor and non-motor variants exist. Four characteristic different time courses can be distinguished. In EPC, seizures are replaced by frequently repeated seizure fragments. EPC indicates a feedback loop of excitation and inhibition. Abstract: Epilepsia partialis contina (EPC) in a narrow definition is a variant of simple focal motor status epilepticus in which frequent repetitive muscle jerks, usually arrhythmic, continue over prolonged periods of time. In a broader definition (used in this review) it also includes non-motor manifestations otherwise known as aura continua. EPC may occur as a single episode, repetitive episodes, it may be chronic progressive or non-progressive. It appears as an unusual manifestation of epilepsy in which more typical paroxysmal events are partly or entirely replaced by the sustained repetition of seizure fragments in rapid succession. The minimum duration is defined as one hour but EPC may continue for up to many years. There are multiple possible etiologies which can be local or systemic, including two disease entities, Rasmussen encephalitis and Russian tick-borne spring-summer encephalitis. Among systemic brain disorders, mitochondrial diseases and non-ketotic hyperglycemia are particularly likely to cause EPC whereas stroke is a frequent cause of acute EPC. The symptoms of motor EPC have been interpreted as cortical reflex myocloni but the pathophysiology is probably not uniform for all cases. In pathophysiological terms, EPC seems to represent an oscillation of excitation and inhibition in a feedback loop whose mechanisms are still poorly understood. However, EPC only seems to occur rarely in an otherwise healthy brain. Treatment has to take account of the etiology but, in general, EPC tends to be drug-resistant. Epilepsy surgery is often indicated in Rasmussen encephalitis.